2020
DOI: 10.3892/ijo.2020.5069
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑103a‑3p promotes metastasis by targeting TPD52 in salivary adenoid cystic carcinoma

Abstract: Salivary adenoid cystic carcinoma (SACC) exhibits slow continuous growth, frequent local recurrences and a high incidence of blood metastasis, with advanced lung metastasis frequently occurring and being among the primary causes of mortality. MicroRNAs (miR) serve a significant role in the initiation and development of cancer and may be tumour-specific molecular targets. However, the role of miR-103a-3p in SACC remains largely unknown. In the present study, the expression levels of miR-103a-3p and tumour prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Overexpression of hsa-miR-103a-3p is associated with the metastasis of breast cancer (Chang et al, 2016) and many other types of cancer (Liang et al, 2015;Fu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of hsa-miR-103a-3p is associated with the metastasis of breast cancer (Chang et al, 2016) and many other types of cancer (Liang et al, 2015;Fu et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of these genes in cancer progression is supported by previous studies. Fu et al reported that TPD52, targeted by mir-103a-3p, could affect the progression of salivary adenoid cystic carcinoma [ 45 ]. Further, Shi et al found that the miR-185-5p/TPD52 axis was associated with radiation sensitivity of TNBC [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported that the lncRNA MRPL23-AS1 promoted cystic carcinoma lung metastasis ( 30 ). In addition, miR-21 ( 31 ), miRNA-140-5p ( 32 ), miR-24-3p ( 33 ), miR-93-5p ( 34 ), miR-125a-5p ( 35 ), and miR-103a-3p ( 36 ) have been reported in cancer in recent years.…”
Section: Discussionmentioning
confidence: 99%